1997
DOI: 10.1007/bf00942043
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of iodinated contrast media on different rabbit arteries in vitro

Abstract: Vasoconstriction caused by iodinated contrast media (CM) has been considered specific for the renal artery only. We examined the vascular effect of CM in rabbit carotid, aorta, renal, iliac, mesenteric and celiac arteries and found that other arteries also respond with a contraction to CM. Isolated arterial rings were exposed to diatrizoate (high osmolar CM), iohexol (low osmolar CM) or glucose solution, and the isometric contraction response was expressed as percentage of an initial KCl control contraction. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Arm pain associated with contrast medium injection is reported frequently as a mild and transient reaction in people. Moreover, there is evidence that contrast medium can exert a direct effect on the vasculature, including vasospasm and constriction 11 . Because the horses that developed a transient change in heart rate and blood pressure experienced tachycardia and hypertension, we suspect that this was related to peripheral vasoconstriction and a systemic response to localized pain in the limb where contrast injection occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Arm pain associated with contrast medium injection is reported frequently as a mild and transient reaction in people. Moreover, there is evidence that contrast medium can exert a direct effect on the vasculature, including vasospasm and constriction 11 . Because the horses that developed a transient change in heart rate and blood pressure experienced tachycardia and hypertension, we suspect that this was related to peripheral vasoconstriction and a systemic response to localized pain in the limb where contrast injection occurred.…”
Section: Discussionmentioning
confidence: 99%
“…be linked to another phenomenon such as an ‘osmotic effect,’ that may increase the hepatic intravascular water content following the intravenous infusion of the contrast agent?‘Osmotic’ differences may be a plausible argument. Although it remains a speculation and further basic studies for the explanation of the practical phenomenon are required, different vasomotor reactions of contrast media have been observed in vitro as well as in animal models (30,31). Rauch et al showed vasodilatation of superior mesenteric artery and coelic trunk in rabbit induced by the application of iodinated contrast agent (31).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed severe arterial thrombosis following tourniquet application and i.a. catheterisation (haematoma and spasm) should also be considered [21,60,169]. Tourniquet use was thought to be the cause and more recent studies without the tourniquet report no severe complications [165,166,168].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Other potential complications of i.a. catheterisation (haematoma and spasm) should also be considered [21,60,169].…”
Section: Intra-arterialmentioning
confidence: 99%